Last Province Aboard:: New Brunswick and National Medicare - Marchildon, Gregory; O'Byrne, Nicole (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2013)
Introduced as a federal-provincial cost-sharing program in the 1960s, medicare aligned ideologically with Premier Louis J. Robichaud’s Equal Opportunity program. New Brunswick was one of the first Canadian provinces to support the adoption of universal healthcare, but it was the last province to implement medicare. This article examines the federal-provincial negotiations surrounding medicare in order to shed light on the scope of Robichaud’s program of Equal Opportunity, to re-evaluate the last years of the Robichaud administration, and to explore why the Progressive Conservative government of Richard Hatfield was responsible for the implementation of medicare in New Brunswick.